Exploring the link between pyrethroids exposure and dopaminergic degeneration through morphometric, immunofluorescence, and in-silico approaches: the therapeutic role of chitosan-encapsulated curcumin nanoparticles - Alotaibi, Badriyah S.; Abdel-Rahman Mohamed, Amany; Abd-Elhakim, Yasmina M.; Noreldin, Ahmed E.; Elhamouly, Moustafa; Khamis, Tarek; El-Far, Ali H.; Alosaimi, Manal E.; Dahran, Naief; Alqahtani, Leena S.; Nicotra, Mario; El-Gamal, Mohamed; et al. (Frontiers in Pharmacology, 2024)
The study addressed the hallmarks of the pathophysiology of Parkinson's disease upon oral exposure to fenpropathrin (FNE), mainly the alteration of dopaminergic markers, oxidative stress, and molecular docking in rat models. In addition, the protective effect of curcumin-encapsulated chitosan nanoparticles (CRM-Chs-NPs) was also assessed. In a 60-day trial, 40 male Sprague Dawley rats were divided into 4 groups: Control, CRM-Chs-NPs (curcumin-encapsulated chitosan nanoparticles), FNE (15 mg/kg bw), and FNE + CRM-Chs-NPs. FNE exposure induced reactive oxygen species generation, ATP production disruption, activation of inflammatory and apoptotic pathways, mitochondrial function and dynamics impairment, neurotransmitter level perturbation, and mitophagy promotion in rat brains. Molecular docking analysis revealed that FNE interacts with key binding sites of dopamine synthesis and transport proteins. On the other hand, CRM-Chs-NPs mitigated FNE's toxic effects by enhancing mitochondrial dynamics, antioxidant activity, and ATP production and promoting antiinflammatory and antiapoptotic responses. In summary, FNE appears to induce dopaminergic degeneration through various mechanisms, and CRM-Chs-NPs emerged as a potential therapeutic intervention for protecting the nervous tissue microenvironment.